Preoperative radiomic signature based on CT images for noninvasive evaluation of localized nephroblastoma in pediatric patients - Ma, Xiao-Hui; Yang, Jing; Jia, Xuan; Zhou, Hai-Chun; Liang, Jia-Wei; Ding, Yu-Shuang; Shu, Qiang; Niu, Tianye (Frontiers in Oncology, 2023)
Background Nephron sparing nephrectomy may not reduce the prognosis of nephroblastoma in the absence of involvement of the renal capsule, sinus vessels, and lymph nodes, However, there is no accurate preoperative noninvasive evaluation method at present. Materials and methods 105 nephroblastoma patients underwent contrast-enhanced CT scan between 2013 and 2020 in our hospital were retrospectively collected, including 59 cases with localized stage and 46 cases with non-localized stage, and then were divided into training cohort (n= 73) and validation cohort (n= 32) according to the order of CT scanning time. After lesion segmentation and data preprocessing, radiomic features were extracted from each volume of interest. The multi-step procedure including Pearson correlation analysis and sequential forward floating selection was performed to produce radiomic signature. Prediction model was constructed using the radiomic signature and Logistic Regression classifier for predicting the localized nephroblastoma in the training cohort. Finally, the model performance was validated in the validation cohort. Results A total of 1652 radiomic features have been extracted, from which TOP 10 features were selected as the radiomic signature. The area under the receiver operating characteristic curve, accuracy, sensitivity and specificity of the prediction model were 0.796, 0.795, 0.732 and 0.875 for the training cohort respectively, and 0.710, 0.719, 0.611 and 0.857 for the validation cohort respectively. The result comparison with prediction models composed of different machine learning classifiers and different parameters also manifest the effectiveness of our radiomic model. Conclusion Logistic Regression model based on radiomic features extracted from preoperative CT images had a good ability of noninvasively prediction of nephroblastoma without renal capsule, sinus vessels, and lymph nodes involvement, and had the potential to help make surgical decisions for precise treatment.